Building a digital library on research into mineralizing vesicles: a systematic review-based approach - Chaves Filho, Gildacio Pereira; de Andrade Tavares, Pedro; de Jesus, Ananda Fernanda [UNESP]; Ciancaglini, Pietro; Segundo, José Eduardo Santarem; Ramos, Ana Paula (Springer Nature, 2025)
This systematic review consolidates current research on mineralizing extracellular vesicles, or matrix vesicles (MVs), including their isolation, characterization, and role in physiological and pathological calcification. We searched PubMed/Medline, Scopus, and Web of Knowledge by employing the keywords “matrix vesicles” or “collagenase-released matrix vesicles” or “mineralizing vesicles” and publishing years from 2000 to 2023. Seventy-one studies met the inclusion criteria. The studies described different experimental protocols, especially with respect to methods for isolating MVs, wherein digestion with collagenase combined with centrifugation was the most used. The studies employed characterization techniques, including the determination of alkaline phosphatase (ALP) and transmission electron microscopy (TEM), to assess the functionality, size, and morphology of MVs. MVs contain key proteins such as ALP, annexins, and osteocalcin, along with calcium and phosphate ions, which are all critical for precipitating apatite. In the studies, evaluation of ALP activity revealed that MVs are more effective for mineralization than their parent cells and, hence, a valuable tool to regenerate bone and to engineer tissues. On the other hand, MVs play an essential role in pathologies, and the studies showed how they contribute to vascular calcification. Despite the therapeutic potential of MVs, isolation methods and characterization protocols vary across the studies, so standardized methods are needed. We have consolidated the data resulting from this systematic review in an open digital library on MVs with free access to all researchers. The users of the digital library can apply filters and taxonomy to find and interconnect the data resulting from the review.
Keywords: Alkaline phosphatase; Bone regeneration; Matrix vesicles; Mineralization; Mineralizing vesicles; Pathological calcification